Hospitalizations in Brazil according to National Health Survey estimates, 2013 and 2019 - Andrade, André Oliveira; Jesus, Sandra Rêgo de; Mistro, Sostenes (Revista de Saúde Pública, 2023)
OBJECTIVE: To c ompare t he profile a nd prevalence of hospitalizations i n B razil b ased on estimates from the National Health Survey (PNS), 2013 and 2019. METHODS: A cross-sectional study that used data from the 2013 PNS and the 2019 PNS. The outcome was having been hospitalized for 24 hours or more in the last 12 months. We calculated the proportion of the population in different categories of age group, presence or absence of chronic diseases, and perception of health status. We estimated the total number of hospitalizations and the proportion corresponding to each category of age group, chronic disease, and perceived health status. We calculated the prevalence of hospitalization according to geographic, socioeconomic, and health conditions. We compared the estimates of two editions of the PNS using Student’s t-test for independent samples. We considered significant differences when the p-value was less than 0.01. And finally, we compared hospitalization estimates with administrative data to assess data consistency. RESULTS: We observed that the proportion of chronically ill people in the population increased from 15.04% to 31.48%. This group was responsible for 36.76% of the total number of hospitalizations in 2013 and 57.61% in 2019. The prevalence of hospitalizations increased significantly between the two surveys and the increases were higher in the Southeast region and among people who have private health insurance. A discrepancy was found between administrative data and survey estimates. Obstetric hospitalizations and health insurance hospitalizations were underestimated. CONCLUSION: There was an increase in overall hospitalization rates in the period between the PNS 2013 and PNS 2019, especially among people with better access to health services. The hospitalization profile also changed—in the 2013 PNS, hospitalizations of people without chronic diseases predominated. This was reversed in PNS 2019.